The issue of the military : the UN's experience of demobilization, disarmament and reintegration in Southern Africa - Alden, Chris (My University, 1996)
This article will analyse the United Nations' experience of demilitarization in Southern Africa with reference to the issues surrounding the transition from an emergency situation to a developmental context. The three UN peace support operations in Southern Africa, namely Namibia, Mozambique and Angola, will be examined to assess the international organisation's role in that process. In so doing, the article highlights a number of themes, including the importance of developing a regional approach to demilitarization; the imperative of cooperation both within the UN itself and with the international donor and NGO community as a whole; and the need to develop a greater understanding of the efficacy of "targeting" demilitarization programmes towards excombatants in light of the broader goals of demilitarization.
African Studies Seminar series. Paper presented October, 1996.
Keywords: Disarmament. Southern Africa; Southern Africa. Armed forces. Demobilization.; United Nations. Southern Africa.